Machine Tool Modelling and Profile Following Performance - Whalley, R. (2008)
The axis drive of a milling machine is considered. Modelling methods enabling the inclusion of the dynamics of the relatively lumped and physically dispersed elements of the system are proposed. A model of the x-axis drive of the machine tool system is constructed. The responses of the system to deterministic inputs under profile following conditions are presented. Machine tool error, tracking accuracy, and surface finish predictions are investigated. Adverse machining operations are identified following geometrical, input signal, amplitude and frequency changes.